Public Health Mentorship Programme: An Intervention Model to Strengthen Health Service Delivery - Owhonda , Golden Chukwuemeka; Dakum, Patrick Sunday; Mensah , Charles; Olupitan, Olayemi Kinmilola; Kanee, Rogers Bariture; Edewor, Ufuoma; Jr, Eric Osamudiamwen Aigbogun (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
The Clinical Mentorship Programme (CMP) is an organised form of PHM programme that was deployed as a pioneer public health intervention and modelled to support existing interventions and other ongoing strategies to catalyse better outcomes in Rivers State, Nigeria's HIV Control Programme. Public Health Mentorship has the potential to change the current trends for healthcare systems struggling with resource constraints, terrain difficulties, and capacity to meet ever-growing needs in service delivery. CMP as a form of PHM is largely untested, particularly in Nigeria. It is a structured intervention designed to supplement efforts to bridge the huge unmet needs in HIV service delivery in a low-resource setting characterised by difficult terrain and security challenges.The rationale was to catalyse quality improvement in targeted indicators through locally tested initiatives, to construct the capacity of local teams, to promote a problem-solving attitude at the site level, and to strengthen team effort between the Institute of Human Virology, Nigeria, Government Agencies, and the beneficiary community. Beginning around July 2019, the CMP was deployed in the State HIV control programme. The SCMs were selected as medical professionals and educated to have the necessary skills to develop personnel and raise the standard of the HIV control programme. Two years after the CMP's implementation, team capacity was successfully established in a team command structure, resulting in improvements in key performance programme indicators. Within two years of its implementation, the CMP accelerated and supported the successful reduction of unmet treatment needs in the Rivers State HIV Control Programme. It is also suggested that it be adapted in other public health programmes as a form of Public Health Mentorship to optimise service delivery in areas with high unmet need.